2015
DOI: 10.1159/000441274
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Probiotics for Preterm Infants: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Necrotizing enterocolitis (NEC) is a major morbidity and cause of mortality in preterm neonates. Probiotics seem to have a beneficial role in preventing NEC, which is confirmed in meta-analyses of randomized controlled trials (RCTs). We therefore aimed to review and confirm the efficacy of probiotics in preterm neonates obtained in observational studies. Objective: To assess the effects of prophylactic probiotics in preterm infants. Methods: A meta-analysis was performed searching PubMed, EMBASE, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 29 publications
7
66
0
5
Order By: Relevance
“…Olsen et al [73] included 12 observational studies with 10,800 premature neonates (5,144 receiving prophylactic probiotics and 5,656 controls). The meta-analysis showed a significantly decreased incidence of NEC (RR 0.55, 95% CI 0.39-0.78) and mortality (RR 0.72, 95% CI 0.61-0.85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olsen et al [73] included 12 observational studies with 10,800 premature neonates (5,144 receiving prophylactic probiotics and 5,656 controls). The meta-analysis showed a significantly decreased incidence of NEC (RR 0.55, 95% CI 0.39-0.78) and mortality (RR 0.72, 95% CI 0.61-0.85).…”
Section: Discussionmentioning
confidence: 99%
“…To address these investigative questions in preterm infants, especially in ELBW infants, randomized controlled trials (RCTs) are not always easy or ethical to conduct. Instead, well-designed observational studies may be the next practicable method to address these types of questions as they have been shown to provide results similar to RCTs, challenging the belief that observational studies are second-rate [11,12]. They reflect routine practice, which allows for the evaluation of effectiveness and safety in large populations that include ELBW patients who are under-represented in, or completely excluded from RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of these studies concluded that probiotics decrease the risk of NEC and death, but not sepsis (Table 2) [55]. Cohort studies of probiotics in premature infants have yielded strikingly similar results (Table 2) [56]. Although these trials utilized differing doses and probiotic strains, it appears that doses of ≥10 9 microbes per day are more beneficial than lower doses, that combinations of probiotics may have advantages over single organisms, and that probiotics are more effective in premature infants receiving human milk than formula [57].…”
Section: Probiotics For Preterm Infantsmentioning
confidence: 99%
“…Overall, probiotics are reported to significantly reduce the incidence of NEC (5.7% in infants receiving placebo compared with 2.4% in those administered probiotics; number-needed-to-treat = 30) and mortality (6.9% in placebo-treated compared with 4.54% in probiotic-treated groups; number-needed-totreat = 42). A more recent meta-analysis of observational multicenter studies also reported that preterm infants administered either single or multistrain probiotic preparations had a lower incidence of NEC and sepsis (10). Interestingly, Baucells et al (68) carried out a systematic review of randomized controlled trials that looked at the effect of various probiotic compounds and mixtures on the incidence of NEC.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Some studies have shown that the use of functional foods can modulate the composition and function of the gut microbiome as a way to alleviate symptoms and signs of IBD, irritable bowel syndrome (8), and colic in infants (9) and to prevent NEC in premature newborns (10).…”
Section: Introductionmentioning
confidence: 99%